Gift Giving, Guanxi and Illicit Payments in Buyer–Supplier Relations in China: Analysing the Experience of UK Companies - Millington, Andrew (Journal of business ethics, 2005)
This paper explores the relationship between gift giving, guanxi and corruption through a study of the relationships between UK manufacturing companies in China and their local component suppliers. The analysis is based on interviews in the China-based operations of 49 UK companies. Interviews were carried out both with senior (often expatriate) staff and with local line managers who were responsible for everyday purchasing decisions and for managing relationships with suppliers. The results suggest that gift giving is perceived to be a significant problem in UK-owned companies in China. However the relationship between these payments and established understanding of gift giving within guanxi-networks appears to be weak. Gift giving appears to be associated with illicit payments, corruption and the pursuit of self-interest. Firms seek to reduce the incidence of illicit transactions by changing staff roles, instituting joint responsibilities, which include the separation of different aspects of sourcing/purchasing, ineasing the involvement of senior staff in the process and through the education of employee and suppliers.